A Minimal tight-binding model for ferromagnetic canted bilayer manganites - Baublitz, M; Lane, C; Lin, Hsin; Hasnain Hafiz; Markiewicz, R S; Barbiellini, B; Sun, Z; Dessau, D S; Bansil, A (arXiv.org, 2014)
Half-metallicity in materials has been a subject of extensive research due to its potential for applications in spintronics. Ferromagnetic manganites have been seen as a good candidate, and aside from a small minority-spin pocket observed in La\(_{2-2x}\)Sr\(_{1+2x}\)Mn\(_{2}\)O\(_{7}\) \((x=0.38)\), transport measurements show that ferromagnetic manganites essentially behave like half metals. Here we develop robust tight-binding models to describe the electronic band structure of the majority as well as minority spin states of ferromagnetic, spin-canted antiferromagnetic, and fully antiferromagnetic bilayer manganites. Both the bilayer coupling between the MnO\(_2\) planes and the mixing of the \(|x^2 - y^2>\) and \(|3z^2 - r^2>\) Mn 3d orbitals play an important role in the subtle behavior of the bilayer splitting. Effects of \(k_z\) dispersion are included.